Endovascular therapy for iatrogenic occlusion of the popliteal artery after complex total knee arthroplasty: A case report - Imam T.P. Ritonga, MD; Giuseppe Asciutto, MD, PhD; Kevin Mani, MD, PhD, FEBVS; Yousef Shehada, MD; Marco Virgilio Usai, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Iatrogenic arterial injury is an infrequent but limb-threatening complication of total knee arthroplasty (TKA). Open surgical reconstruction may not always be feasible or optimal, particularly in patients who have recently just undergone complex TKA procedures. In this report, we describe the treatment of a patient who developed popliteal artery occlusion following a complex TKA procedure performed the previous day. Although endovascular advancement allows comprehensive endovascular treatment of acute limb ischemia, their application in the context of iatrogenic arterial injury after TKA is limited, with only a few cases documented. This case is notable due to the presence of both penetrating trauma to the popliteal artery and subsequent thrombosis of the artery. These complications were successfully managed entirely through endovascular therapy, employing AngioJet rheolytic thrombolysis and the implantation of a covered stent. This case adds to the growing body of evidence supporting the use of endovascular techniques for managing this rare and complex complication of TKA.